A Godly Man and a Manly God: Resolving the Tension of Divine Masculinities in the Bible - Will Moore (Journal for Interdisciplinary Biblical Studies, 2021)
In the Hebrew Bible, God epitomises an ideal hegemonic masculinity: sexless but reproductive, in control of his creation, and hypermasculine when engaging with his feminised followers. As such, the Gospel writers depict Jesus as the Son of God with this, as well as the masculine ideals of the Greco-Roman world, in mind. Ultimately, this causes a tension of divine masculinities, which is particularly exposed in the act of crucifixion where two different divine masculinities are at play. Using the queer and social-scientific methodology of Butler and Connell respectively, I argue that these biblical divine masculinities disturb dominant constructions of gender in the ancient world and followers of Christianity might be called to do the same.